Strategies For Entrepreneurship And Innovation - A Case Study - Ghosh, Jyotirmoy; Swamy, Anjaneya (Ushus Journal of Business Management, 2010)
Entrepreneurs all over the world have contributed to the economic development of their region. They play a major role not only in organizing production, but in a broader sense, promote the process of economic development. The function of an entrepreneur is to reform or revolutionize the pattern of production by exploiting an invention or more generally an untried technology possibly for producing a new commodity or producing an old one in a new way, by opening up a new source of supply of raw materials or developing a new market. The factor responsible for change, development and ultimately economic growth is innovation. Innovation is the key for not only in developing, new products or (services) for the market but also in stimulating investment interest in the new ventures being created. Innovation is the principal ingredient of entrepreneurship. Tourism is a smokeless service industry as it consumes less energy and pollutes least compared to any manufacturing industry. United Nations, World Tourism Organization and Department of Tourism Government of India have bestowed 'Industry' status to tourism in order to enable the industry to enjoy all the incentives and grants offered to industries in general. Currently tourism enjoys the pride of being the second largest growing industry next to IT. Tourism promotes better national and international relationship through cross culture interaction. Backward areas with its residing people can be uplifted with tourism activities without investing in capital intensive industries. The importance of tourism industry is more pronounced as it employs the largest number of manpower and earns the maximum foreign exchange. Being a part of the services sector tourism has also given birth to innumerable entrepreneurs who thrived on their personal creativity and innovativeness. An effort has been made in this paper to present the career progress of Captain Gopinath who is undoubtedly one of the greatest tourism/ entrepreneurs of the 21s1 century in India. Gopinath sacrificed a secured career in the Indian armed forces to strike on his own and in the process established a number of entrepreneurial establishments in aviation and tourism industry. Captain Gopinath neither followed management theories nor had formal management qualifications. But his actions and achievements had close resemblance with the deliberations of the best management gurus. A study have been conducted to compare the behaviors, actions and achievements of Captain Gopinath with the works of great authors who have researched and contributed over the years on 'Entrepreneurship'.